The Chilean Constitutional Process Narrated Through a Spiral - Adriana Suárez Delucchi; Victoria Rivera Ugarte (Studies in Social Justice)
Building on an intertwined spatiotemporal weaving of reckoning-repairing-reworlding, this article analyses the constitutional process experienced in Chile between 2019-2023. Inspired by the sociology of image as a methodological tool and following a narrative that takes the shape of a spiral, we examine a series of photographs representing different layers in this ongoing process. In October 2019, the largest demonstrations in Chile’s history sparked long-brewing demands for social and ecological transformation. The unsustainable pressure pushed political parties to call for a constitutional referendum where the population overwhelmingly voted to overturn the charter inherited from Augusto Pinochet’s regime, and so the process of drafting a new text began. Following the rejection of two drafts, the constitutional process is, for now, closed. Yet, we claim that embracing a failure narrative is not only futile, but misleading, and we propose to see these events in terms of their potential for conceptualising and enacting transformative futures. Drawing on decolonial, anti-colonial, and Indigenous scholarship, this essay focuses mainly on 2019’s uprising and the first constitutional process (2021-2022) examining demands for Indigenous transformation – and the possibilities this case offers resistance movements elsewhere and “elsewhen.”